The Effect of Statistical Data Base Method on Improving Basketball Playing Skills For Adolescent Athletes Aged 13-14 Years - Azahra, Fikra; Lubay, Lukmannul Haqim; Ramadhan, Kevin; M. Hafid Qolbi (JURNAL PENJAKORA, 2025)
This study aims to examine the effectiveness of a game-understanding-based training method combined with statistical database evaluation in improving basketball playing skills among adolescent athletes aged 11–14 years. The research employed a quasi-experimental design with a pre-test post-test control group. A total of 20 athletes were selected purposively from basketball clubs in Bandung Regency. The instruments used were based on game performance statistics derived from FIBA.LIVESTATS and measured using the Game Performance Assessment Instrument (GPAI). Data analysis was conducted using the paired sample t-test as a parametric test. The results showed a significant improvement in the experimental group (p = 0.000 < 0.05), indicating enhancements in both technical and tactical playing skills. These findings suggest that a statistical data-based approach can enhance the quality of training and the accuracy of performance evaluation in adolescent athletes. The study recommends integrating data-driven evaluation systems into long-term athlete development programs for youth.